2020
DOI: 10.1039/d0dt03638b
|View full text |Cite
|
Sign up to set email alerts
|

The geometric and electronic structures of a Ag13Cu10(SAdm)12X3 nanocluster

Abstract: A Cu-rich alloy nanocluster [Ag13Cu10(SAdm)12]X3 is reported, and its geometric and electronic structures are further determined via theoretical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…S2†). This was similar to the reported Ag 74 (CCPh) 44 , 48 Ag 13 Cu 10 (C 10 H 15 S) 12 X 3 , 18 and [Au 1 Ag 26 (SR) 18 Cl], 49 which indicated that phosphine ligands played a role in the synthesis process. In addition, phosphine ligands with different substituting groups ( i.e.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…S2†). This was similar to the reported Ag 74 (CCPh) 44 , 48 Ag 13 Cu 10 (C 10 H 15 S) 12 X 3 , 18 and [Au 1 Ag 26 (SR) 18 Cl], 49 which indicated that phosphine ligands played a role in the synthesis process. In addition, phosphine ligands with different substituting groups ( i.e.…”
Section: Resultssupporting
confidence: 90%
“…The total structure could be divided into two parts, including a Ag 12 core and a Ag 3 Cu 12 (SR) 18 (CH 3 COO) 3 shell. In comparison, the reported NCs containing 27 metal atoms, such as Ag 27 51 and Au 1 Ag 26 , 49 or the NCs containing close to 27 metal atoms, such as Ag 13 Cu 10 , 18 Ag 25 Cu 4 31 and Ag 25 , 52 typically presented an icosahedral M 13 kernel. The reported Au 27 Cd 1 also consisted of a bi-icosahedral kernel, which was made up of two icosahedral Au 13 units sharing a common triangular Au 3 face.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this respect, the kinetics during the formation of bimetallic clusters has attracted big interest. Especially the temporal evolution of their electronic and geometric structure was investigated. , Observing the formation of such bimetallic clusters during deposition and the concomitant phase separation on the nanoscale in real-time was hitherto accessed by molecular dynamics (MD) simulations . In detail, the system silver (Ag)–copper (Cu) alloy has received considerable attraction.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Recently, Bao et al prepared the [Ag 13 Cu 10 (SAdm) 12 ] 3+ (Adm = –SC 10 H 15 ) NC, which has a Ag 13 core and a Cu 10 (SAdm) 12 shell. 22 …”
Section: Introductionmentioning
confidence: 99%